2023
DOI: 10.1038/s41598-023-32235-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal growth on high-aspect-ratio diamond nanopillar arrays for biosensing applications

Abstract: Monitoring neuronal activity with simultaneously high spatial and temporal resolution in living cell cultures is crucial to advance understanding of the development and functioning of our brain, and to gain further insights in the origin of brain disorders. While it has been demonstrated that the quantum sensing capabilities of nitrogen-vacancy (NV) centers in diamond allow real time detection of action potentials from large neurons in marine invertebrates, quantum monitoring of mammalian neurons (presenting m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In particular, the novolac-type photoresist can be fabricated with a submicrometer-scale pattern in a large area using a general lithography system. Submicron-scale structures with high aspect ratios, such as nanopillar arrays, are highly demanded for biological applications or optical devices. ,, A novolac-type photoresist with submicrometer hole patterns was fabricated on SiO 2 , as shown in Figure c. The photoresist-covered areas were selectively etched via the HF gas-phase surface treatment, as shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the novolac-type photoresist can be fabricated with a submicrometer-scale pattern in a large area using a general lithography system. Submicron-scale structures with high aspect ratios, such as nanopillar arrays, are highly demanded for biological applications or optical devices. ,, A novolac-type photoresist with submicrometer hole patterns was fabricated on SiO 2 , as shown in Figure c. The photoresist-covered areas were selectively etched via the HF gas-phase surface treatment, as shown in Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the novolac-type photoresist can be fabricated with a submicrometer-scale pattern in a large area using a general lithography system. Submicron-scale structures with high aspect ratios, such as nanopillar arrays, are highly demanded for biological applications 29 31 or optical devices. 10 , 11 , 32 A novolac-type photoresist with submicrometer hole patterns was fabricated on SiO 2 , as shown in Figure 2 c. The photoresist-covered areas were selectively etched via the HF gas-phase surface treatment, as shown in Figure 2 d. Additionally, vertical nanopillar arrays with the same diameter as the photoresist holes were fabricated on SiO 2 , as shown in Figure 2 e. Therefore, deep microfabrication at the submicron-scale structure was demonstrated using the HF gas-phase anisotropic etching technique with a novolac-type photoresist.…”
Section: Resultsmentioning
confidence: 99%
“…Top-down approaches have focused on forming nanopillar structures by etching diamond blocks or diamond films, but there has not been a cost-versus-quality solution for the preparation of etch masks. Most of the nanopillar etching masks are currently prepared by electron beam lithography (EBL) technique. , Ali Momenzadeh et al prepared a tapered diamond nanopillar array using EBL and found that this tapered nanopillar can effectively increase the photon collection efficiency by more than 10 times. Although this technique enables the preparation of nanoscale-sized etch mask arrays, , its high fabrication cost makes the technique difficult to be widely used.…”
Section: Introductionmentioning
confidence: 99%
“…11 Because of the unique properties of nanopillars such as high surface area-to-volume ratio, biocompatibility, controllability of their geometry and material, and the availability of several techniques for their fabrication, nanopillar platforms are being developed for a variety of fundamental research and commercial clinical applications 12 in the biomedical field. 13 For example, in recent studies, nanopillars arrays have been used as platforms for biomolecule delivery 14,15 , building blocks of state-of-the-art nanobioelectronics for neuron 16,17 and cardiac electrophysiology [18][19][20][21] , platforms for cancer malignancy detection 22 , and modulation of cell and nuclear mechanics. [23][24][25] Due to the growing list of applications of nanopillars in the biomedical field, several studies have focused on characterizing the interface between nanopillars and cells with the goal of controlling cell behaviors.…”
Section: Introductionmentioning
confidence: 99%